PVP-LiClO4: CdTe quantum dots gel polymer electrolyte as the key element for simplified photosupercapacitor devices - Peinado-Pérez, Juan José; Sánchez-Caballero, Abraham; Martín-Jiménez, Francisco de Paula; Algarra, Manuel; Jiménez-Jiménez, José; López-Escalante, María Cruz (Elsevier, 2026)
Electrolytes in the form of polymer gels are of great interest to industry due to their versatility, which is increased by the incorporation of nanofillers. The doctor blade technique was used to add different amounts of cadmium telluride quantum dots (CdTe QDs) (0 %, 2.0 %, 5.0 %, 7.0 % and 9.0 % by weight) to a polyvinylpyrrolidone (PVP) base containing lithium perchlorate (PVP-LiClO₄). The results show that the presence of quantum dots modifies the surface morphology and causes changes in the vibrational signals, particularly those of the carbonyl group. It also modifies the absorption spectra of the electrolytes, affecting their direct band gap (from 4.92 eV to 4.64 eV) and indirect band gap (from 5.20 eV to 5.12 eV). Impedance spectroscopy analysis (Z' y Z'), performed in the dark, shows that increasing the amount of nanofillers in the electrolyte reduces its overall resistance due to the increase in carrier concentration. However, under illumination, blocking conditions are reached as the generated charge carriers recombine with the polymer vacancies, thereby confining the lithium ions. The flow of photogenerated electrons can be harnessed when the electrolyte is assembled with a bismuth vanadate (BiVO₄) photoanode, thanks to complementary band structures, and a poly(3,4-ethylenedioxythiophene) (PEDOT:PSS) cathode. The result is a device that can be characterized as both a solar cell and a photocapacitor. Overall efficiency improves when the device is characterized with unfilled electrolytes and 9.0 wt% CdTe QDs. The efficiency of the solar cell increases from 0.0075 % to 0.0307 %, and the overall efficiency of the photocapacitor increases from 0.028 % to 0.047 %.
Keywords: Células solares; Coloides poliméricos; Materiales nanocompuestos; Photosupercapacitor, solar cells; CdTe quantum dots; Gel polymer nanocomposites; Electrolyte